What Drives Intention to Stay Longer? Evidence Hotel Customer Indonesia - Juliana Juliana; Arifin Djakasaputra; Rosianna Sianipar; Nova Bernedeta Sitorus; Sandra Maleachi; Gunawan Prabowo (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2022)
Hotels have become a place associated with tourism and are needed when people travel for more than one night. Each prospective visitor has different criteria in choosing a hotel or inn, one of which is a measure of the application of health and safety, increasing customer satisfaction, satisfying service and increasing customer value. The purpose of this study was to examine whether customer value, health and safety, service quality, customer satisfaction had an effect on intention to stay longer. Data analysis in this study using PLS-SEM. The population in this study are consumers who have stayed at hotels in Indonesia. This study used 160 respondents to fill out a questionnaire with a Likert scale of 1-6. The sampling technique used is simple random sampling. The results showed that customer value, health and safety, service quality, customer satisfaction had a positive and significant effect on intention to stay longer. Furthermore, this research provides discussion, implications and conclusions. This study provides theoretical and managerial implications for understanding respondents' intentions to stay longer in hotels.Keywords: customer value, health and safety, service quality, customer satisfaction, intention to stay longer